Carbon fiber recovery using subcritical and supercritical fluids for chemical recycling of thermoset composite materials - Morales Ibarra, Rodolfo (2014)
Recovery of carbon fibers by recycling thermoset epoxy-matrix composites is highly desirable from both economic and environmental perspectives. This reduces waste disposal of scrap from production parts and end-of-life products. In this research, benzyl alcohol and water in subcritical and supercritical conditions, with and without addition of tripotassium phosphate (K3PO4) as a decomposition reaction catalyst, were used to recover carbon fibers from composite materials for potential reuse in high performance components; while, in the literature review, the composite materials and their manufacturing processes were revisited, as well as the legal implications of end-of-life composite components, justifying the need for a thermoset composite materials recycling research project. In the experimental section of this research, the reaction temperature and time duration were the experimental parameters. The methods were evaluated by measurement of the decomposition rate of epoxy resin, which reached up to 89.1% and 93.7% with supercritical water and subcritical benzyl alcohol, respectively. The samples were characterized by scanning electron microscopy (SEM). SEM analysis showed complete separation of the composites as indicated by the clean recovered carbon fibers.